`A Fine Subject to Expatiate Upon.' British Foreign Policy and the Rhetoric of National Honour, 1830-1880. - Twamley, Zachary Jonathan (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2024)
This thesis analyses the rhetoric of national honour in British foreign policy, during the period 1830 to 1880. National honour?s status as an understated, understudied subject will be addressed, yet this thesis will not attempt to position national honour as the cause of conflict. Instead, it will draw from material in the public sphere ? including Parliamentary debates, public speeches, and Britain?s expanding media industry ? to demonstrate that contemporaries used national honour?s extensive lexicon, both to explain policy decisions and to criticise their political opponents. This thesis will explicate national honour from British foreign policy by considering how this rhetoric was used by contemporaries during periods of foreign policy crisis. It will also measure the extent to which national honour?s rhetoric constrained and facilitated foreign policy. These tasks will be addressed through a case-study approach, with a focus on incidents which did not, generally, result in war, but did compel contemporaries to engage extensively with national honour?s lexicon, and use the available rhetoric to frame their positions. This thesis is structured to provide analysis for national honour?s main rhetorical themes, and is divided into two broad sections; the former is concerned with `miniature? case studies up the period 1850, and the latter examines three individual cases over three remaining chapters. Thus, Chapter One considers how this rhetoric was used by Palmerston during his stewardship of Whig foreign policy, from 1830 to 1841. Chapter Two addresses the concept of insult, and examines contemporary efforts by Whigs and Conservatives to vindicate national honour by acquiring satisfaction during the 1840s. Chapter Three focuses on Anglo-American relations during the contentious period of 1838-1846, wherein themes including insult, conciliation, and compromise were dealt with. Chapter Four concerns the 1861 Trent Affair, and the response to the American insult during the American Civil War. Chapter Five considers British policy during the Schleswig-Holstein crisis, and the conflicting themes of obligation, bluster, and influence. Chapter Six examines Benjamin Disraeli?s policy during the Eastern Crisis of 1875 to 1878, wherein the Prime Minister recast prestige as a surrogate of national honour, and presided over a policy of tense confrontation with Russia. It will be revealed that the rhetoric of national honour could justify policies of confrontation, magnanimity, and the maintenance of the status quo. National honour?s rhetorical power was considerable, but it was not a panacea either for the government or the opposition. There were limits to its influence and effectiveness, which were exposed by complex negotiations or debates on distant issues of scant interest to the British public. Notwithstanding its status as a belief system accepted by the majority, this thesis will demonstrate that national honour was, above all, a politically contested space.
APPROVED